Clean bombs and dirty wars air power in Kosovo and Libya - Gregory, Robert H. (Potomac Books, 2015)
Clean Bombs and Dirty Wars: Air Power in Kosovo and Libya explores how the U.S. public, policymakers, and military services perceived and utilized air power and precision munitions before, during, and after Operation Allied Force in Kosovo in 1999 with incorrect assumptions.